Freedom of belief and Christian mission - Gravaas, Hans Aage, 1961-; Sauer, Christof, 1963-; Engelsviken, Tormod; Kamil, Maqsood, 1965-; Jørgensen, Knud, 1942- (Regnum Edinburgh centenary series, 2015)
Christian mission takes place in a world with increasing interreligious tensions, including violence and persecution. Politics, economics, religion, ethnicity and other factors play a role in these tensions. Christians too are involved in such conflicts, sometimes as those who are persecuted and sometimes as those participating in violence. 'Freedom of religion and belief'is a core value in the UN Human Rights Declaration. At the same time it is a core biblical value. Obstacles to and attacks on freedom of belief are therefore a central concern for witnessing to Christ. The purpose of this volume on Freedom of Belief and Christian Mission is to bring to public attention a broad overview on the history, development and perspectives on the role of mission and freedom of belief and to reflect on these issues within a context of authentic witness in mission.